Protective effects of Phyllanthus phillyreifolius extracts against hydrogen peroxide induced oxidative stress in HEK293 cells - Grauzdytė, Dovilė (PLoS One, 2018)
Phyllanthus phillyreifolius, a plant species indigenous to Reunion Island, is used in folk medicine for treating diarrhea and as a diuretic. In the present study acetone and hydroethanol extracts of P. phillyreifolius were evaluated for their cytotoxicity and antioxidant effects using in vitro (TPC, ABTS, DPPH, FRAP, ORAC) and in cellulo (MTT, DCFH-DA, RT-qPCR) assays. Major compounds were evaluated using UPLC–QTOF–MS. MTT cell viability assay showed low cytotoxicity of extracts towards human embryonic kidney 293 (HEK293) cell line. Both extracts were rich in polyphenols (mainly ellagitannins) and showed high antioxidant potential and intracellular ROS decreasing effect. Preconditioning of HEK293 cells with extracts influenced gene expression of antioxidant enzymes, however ROS level decreasing effect was more related to their capacity to scavenge free radicals and with their reducing power. Strong antioxidant activity of extracts as well as the presence of geraniin supports the use of P. phillyreifolius in traditional medicine.